Marijuana Legalization in Canada: Insights for Workplaces from Case Law Analysis - Lam, Helen (Relations industrielles / Industrial Relations, 2019)
The legalization of marijuana in Canada is expected to have a significant impact on workplaces, requiring the development or updating of company drug-related policies and procedures. To help employment relations stakeholders with this change, recommendations are made based on an analysis of 93 past arbitration/tribunal/court cases involving marijuana-related policy violations, drawn from the Labour Source database. Issues addressed include language and communication of the work rule, reasonableness of drug tests, standard of proof, duty to accommodate, and mitigating factors.Based on the study of those 93 court cases, some recommendations can be formulated. First, employers need to clearly state their drug-related policies, taking into consideration safety-sensitivity and any substance abuse culture. This may include prohibition of possession, use, and distribution of drugs at the workplace or working under the influence, and the need to report any medical drug use that requires accommodation. Drug tests should only be done when there is a bona fide occupational requirement or where safety is a concern, such as post-incident or when there is reasonable suspicion of drug impairment. Also, it is important to understand that positive drug test results can only show past drug use but not the level of impairment or whether the drug was used while on a work shift. Therefore, to support an offence violation and discipline, corroborating evidence from multiple witnesses and sources are often necessary.Supervisors should be trained to identify the characteristics related to marijuana and drug impairment and the procedures to follow when an incident occurs. Employers must be cognizant of the duty to accommodate medical marijuana users or recreational users who are addicted, under human rights protection for disability. Such accommodation may include work reassignment or a leave of absence. In deciding on a penalty, other than past performance and disciplinary records and personal extenuating circumstances, arbitrators may consider rehabilitation situations to assess the prognosis and viability of the employment relationship.Employers and unions are advised to stay abreast of latest developments in the laws, drug test technologies and medical research related to marijuana use.